Analisis Kinerja Keuangan Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan (Bappedalitbang) Kabupaten Deli Serdang - Kamila Kamila; Nida Andina (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The Regional Development Planning Agency, Research and Development (BAPPEDALITBANG) of Deli Serdang Regency is a regional technical institution in the field of regional development planning led by a head of the agency who is under and responsible to the Governor/Regent/Mayor through the regional secretariat. This study aims to assess the financial performance of Bappedalitbang Deli Serdang Regency for five fiscal years. In measuring financial performance, it is more focused on the Budget Realization Report (LRA). The measurement of financial performance is carried out to determine the absorption of the budget and the use of the budget during the five fiscal years on activities that exist in the agency itself. This research uses a qualitative approach with data collection techniques in the form of documentation. The analytical method used is descriptive method with the formula: compatibility analysis of spending which is divided into direct and indirect spending, effectiveness analysis, spending variance analysis, efficiency analysis and spending growth analysis. The results of the analysis show that the financial performance of the Deli Serdang Regency Bappedalitbang from 2019-2022 seen from the shopping compatibility analysis shows poor financial performance, because the total indirect spending is 51% and for direct spending 49%, so it can be said that the Bappedalitbang for the Regency Province Deli Serdang pays little attention to regional development. From the analysis of spending growth in 2019-2022 it is said to be good, because it can be seen that there has been a growth in spending for five years with a total of 1%, with a maximum value of 14% in 2019 and a minimum value of 3% in 2019. 2019-2022 can be said to be good, with a total comparison of 89%. However, judging from the effectiveness ratio of the use of the budget for five years, it can be said to be quite effective with the total ratio reaching 83%. Meanwhile, if viewed from the efficiency ratio, the Bappedalitbang Deli Serdang Regency is said to be quite efficient in using its budget from 2019-2022, with a total of 34 %, so in this case the Deli Serdang Regency Bappedalitbang has been able to make budget savings. Keywords: Financial Performance, shopping compatibility ratio, efficiency, effectiveness, and variance.